The determinants of capital structure for Malaysian construction firms - ﻿Md Rus, ﻿Rohani; ﻿Samiran, ﻿Maslina (2012)
﻿This study examines company specific characteristics that determine the capital structure of construction firms in Malaysia. The sample consists of 37 construction firms that are listed in the main board of Bursa Malaysia from 2003 to 2008. The results are consistent with the Pecking Order theory which advocates that firms prefer internal funding instead of external debts to finance their investment. It also indicates that construction firms will not resort for long term debt once they are stabilized and do not extensively make use of the benefits earned by the incentive of depreciation as tax discounts which imply that trade off theory does not apply among the construction firms in Malaysia. There are two possible explanations for these findings. First, the nature of the construction firm is different from others where all payments are paid progressively by the clients. Therefore, firms will not necessarily issue debts, but they increase their working capital by utilizing their available banking facilities. Second, construction firms prefer to dispose their internal assets to fund their projects in contingency or turbulent situations.